2017
DOI: 10.1007/s11096-016-0418-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-care of long-term conditions: patients’ perspectives and their (limited) use of community pharmacies

Abstract: Background Self-care support is an ‘inseparable’ component of quality healthcare for long-term conditions (LTCs). Evidence of how patients view and use community pharmacy (CP) to engage in self-care of LTCs is limited. Objective To explore patients’ perspectives of engaging in self-care and use of CP for self-care support. Setting England and Scotland. Method Qualitative design employing semi-structured interviews. LTCs patients were recruited via general practitioners (GPs) and CPs. Interviews were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…28 "If the pharmacist just took it on himself I wouldn't be happy, but I would think if the doctor said go and see the pharmacist to discuss it, that would be good" (Lay, diabetes, primary; Twigg et al, 2013) However, the role of CPs in endorsing GP help-seeking was also valued 28 and CP services were more highly regarded when relationships with GPs were poor, access to other services difficult and satisfaction with other healthcare services was low. 40 CP was seen to occupy an isolated and subordinate position rather than one that is fully integrated with the rest of the primary care team. 39 This conflicted with patients' wish for care that is "joined up" i.e.…”
Section: "I Would Go and See The Doctor I Wouldn't Ask These [Cp]mentioning
confidence: 99%
See 2 more Smart Citations
“…28 "If the pharmacist just took it on himself I wouldn't be happy, but I would think if the doctor said go and see the pharmacist to discuss it, that would be good" (Lay, diabetes, primary; Twigg et al, 2013) However, the role of CPs in endorsing GP help-seeking was also valued 28 and CP services were more highly regarded when relationships with GPs were poor, access to other services difficult and satisfaction with other healthcare services was low. 40 CP was seen to occupy an isolated and subordinate position rather than one that is fully integrated with the rest of the primary care team. 39 This conflicted with patients' wish for care that is "joined up" i.e.…”
Section: "I Would Go and See The Doctor I Wouldn't Ask These [Cp]mentioning
confidence: 99%
“…Patients were reported to hold primarily traditional views regarding the division of labour in healthcare [37][38][39] and the dominant perception of CP was seen to be responsibility for medicines supply and over the counter advice for self-limiting conditions. 36 38-40 There was evidence of a lack of clarity about the role of the pharmacist or purpose of CP services, 40 particularly when these contradicted expected and traditional perceptions of the pharmacist encounter. 31 The role of the pharmacist was usually conceptualized, not in isolation, but in relation to beliefs about other roles and responsibilities within the wider healthcare system, primarily those of the GP.…”
Section: Lay Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst evidence has demonstrated positive outcomes from community pharmacy services, uptake and awareness of some of these services have been low. A systematic review of uptake and patient outcomes of remunerated pharmacy services revealed low uptake despite improved clinical and financial outcomes, but this study did not explore patient perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to preserve one’s self-image could also have explained the limited involvement of healthcare professionals in medication work [ 48 , 53 , 66 68 ]. There is some evidence that suggests patients perceive the role of pharmacists as limited to medicines supply [ 26 , 69 – 71 ].…”
Section: Discussionmentioning
confidence: 99%